An analysis of the physiological strain of submaximal exercise in patients with chronic obstructive bronchitis. Issue 4 (August 1975) - Spiro, S G; Hahn, H L; Edwards, R H; Pride, N B
Abstract : An increasing work rate was performed by 40 patients with chronic obstructive bronchitis, split into two groups according to FEV1 (group M, mean FEV1 1-451. and group S, mean FEV1 0-621.), and by 20 normal, non-athletic men of similar age to the patients. Values for cardiac frequency and ventilation were interpolated to standard oxygen uptakes of 0-75, 1-0, and, where possible, 1-5 min-1. The tidal volume at a ventilation of 20 and 30 1 min-1 was also determined. The cardiac frequencies at oxygen uptake of 0-75 and 1-01 min-1 were significantly higher in the patient groups than in the normal men, and were highest in patient group S. The cardiac output when related to the oxygen uptake was in the normal range in all three groups of subjects, so that the patients had smaller stroke volumes than the normal men. Ventilation at oxygen uptakes of 0-75 and 1-01 min-1 was significantly higher in both patient groups than in the normal subjects; there were no significant differences between the two patient groups, Values for dead space/tidal volume ration, alveolar-arterial oxygen gradient, and the percent venous admixture measured during a constant work rate test were significantly greater than normal in the patient groups. Possible factors limiting exercise tolerance in these patients were assessed by extending the increasing work rate test from submaximum to maximum exercise. Changes in blood gas tensions and blood lactate concentrations from resting levels were small, and probably did not limit exercise performance. Measurements at maximum exercise did not add appreciably to the analysis of the disturbed cardiopulmonary function. This study has shown that major disturbances in cardiopulmonary function can be demonstrated without the need for stressing a patient to the limit of his effort tolerance.